2019
DOI: 10.4103/jcd.jcd_389_18
|View full text |Cite
|
Sign up to set email alerts
|

CRA Grid - A preliminary development and calibration of a paper-based objectivization of caries risk assessment in undergraduate dental education

Abstract: Context: Caries risk assessment (CRA) varies between students and faculty due to the subjectivity inherent in the process as well as in the critical thinking skills required for the processing of information. Aims: The aim was to develop a paper-based, grid system, CRA-Grid, to objectivize and standardize risk assessment and to assess its rating agreement with the critical thinking process of the teachers. Settings and Design: The CRA-Grid wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 24 publications
1
5
0
Order By: Relevance
“…Therefore, in order to be more cost-effective, the present study excluded the unchangeable factors, water fluoridation and fluoride supplement and salivary testing for mutans streptococci levels. The results of the present study are consistent with the findings of Intarasompun et al [10] and Ramarao and Sathyanarayanan [13] which also adjusted the full version of caries risk assessment by AAPD by excluding some questions and salivary testing for cost-effectiveness yet also reported effectiveness in preventing dental caries. The IOC index and Cronbach's alpha from the present study registered high values, meaning that the brief-caries risk assessment form was a valid instrument.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Therefore, in order to be more cost-effective, the present study excluded the unchangeable factors, water fluoridation and fluoride supplement and salivary testing for mutans streptococci levels. The results of the present study are consistent with the findings of Intarasompun et al [10] and Ramarao and Sathyanarayanan [13] which also adjusted the full version of caries risk assessment by AAPD by excluding some questions and salivary testing for cost-effectiveness yet also reported effectiveness in preventing dental caries. The IOC index and Cronbach's alpha from the present study registered high values, meaning that the brief-caries risk assessment form was a valid instrument.…”
Section: Discussionsupporting
confidence: 92%
“…The efficacy of the brief-caries risk assessment form is consistent with a previous research paper in Thailand [10] which also excluded the unchangeable factors, salivary test for mutans streptococci levels and oral examination and found that their form had the effectiveness to prevent dental caries. Furthermore, Ramarao and Sathyanarayanan found that excluding the salivary test in the caries risk assessment-grid for school children also prevented dental caries [13]. However, these previous studies administered the form with 2–5-year-old children [10] and school children [13], respectively.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations